Progress update: Crop development of biofortified staple food crops under Harvestplus - Andersson, Meike S.; Saltzman, Amy; Virk, Parminder Singh; Pfeiffer, Wolfgang H. (Rural Outreach Program, 2017)
Over the past 15 years, biofortification, the process of breeding nutrients into food crops, has gained ample recognition as a cost-effective, complementary, feasible means of delivering micronutrients to populations that may have limited access to diverse diets, supplements, or commercially fortified foods. In 2008, a panel of noted economists that included five Nobel Laureates ranked biofortification fifth among the most cost-effective solutions to address global challenges such as reducing hidden hunger. The 2016 World Food Prize was awarded to biofortification. Biofortification involves breeding staple food crops to increase their micronutrient content, targeting foods widely consumed by low-income families in Africa, Asia, and Latin America. The focus is on providing sufficient levels of vitamin A, iron, and/or zinc through these crops, based on existing consumption patterns. HarvestPlus is part of the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH). HarvestPlus works in partnership with more than 200 scientific and implementation organizations around the world to improve nutrition and public health by developing and promoting biofortified food crops that are rich in vitamins and minerals, and providing global leadership on biofortification evidence and technology. Crops bred for higher levels of micronutrients using conventional breeding methods have been released in 26 countries in Africa, Asia and Latin America, and are now being grown and eaten by millions of farmers and consumers. This paper reviews crop development progress and varietal release of primary (major) and secondary (regionally important) staple crops, with a focus on progress in Africa.